3D Carbon Electrode Based Triboelectric Nanogenerator. Issue 8 (15th September 2016) - Kim, Daewon; Pramanick, Bidhan; Salazar, Arnoldo; Tcho, Il‐Woong; Madou, Marc J.; Jung, Eun Sang; Choi, Yang‐Kyu; Hwang, Hyundoo
Abstract : A patterned photoresist is converted into a highly conductive carbon by pyrolysis . Conductive carbon pattern is used as a contact electrode in a triboelectric nanogenerator. The surface of the carbon electrode is either flat or modified with carbon microposts in one instance and with carbon nanofibers in another. It is expected that carbon contact electrodes successfully replace conventional metal contact electrodes.